Associations between body composition and performance in elite endurance athletes - Kettunen, O.; Mikkola, J.; Ihalainen, J. K. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To investigate if elite endurance athletes periodized their body mass (BM) and composition from preparation (T1) to specific preparation period (T2) and if changes in BM and body composition were associated with improved endurance performance.